The fear - Higson, Charles, 1958- (New York : Hyperion, 2012)
In London, after a worldwide sickness infects adults, turning them into zombie-like creatures, DogNut and his crew embark on a deadly mission to find missing friends, as hungry, bloodthirsty grownups lie in wait.
Keywords: Horror stories; Zombies -- Juvenile fiction; Survival -- Juvenile fiction; Wilderness survival -- Juvenile fiction; Zombies -- Fiction; Survival -- Fiction; Wilderness survival -- Fiction; London (England) -- Juvenile fiction; England -- Juvenile fiction; London (England) -- Fiction; England -- Fiction